PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PASIEN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN DI KLINIK MEGA KARTIKA - Ismoerida Ismoerida; Yati Puspitasari Anabanu (Jurnal Manajemen FE-UB, 2019)
This study aims to examine and analyze the effect of service quality and price on patientsatisfaction and its impact on customer loyaltyThe data used in this study are primary data taken from the results of questionnaireresponses by Depok Kartika Mega Kartika clinic patients. The data processing method uses thepath analysis method with the help of SPSS analysis tool version 24. The statistical testing in thisstudy uses a model of goodness of fit test.The results showed that service quality had a positive and significant effect directly orindirectly through patient satisfaction on customer loyalty, price had a positive and significanteffect directly or indirectly through patient satisfaction on customer loyalty and customer loyaltyhad a positive effect directly on customer loyalty .Keywords: Quality of service, price, patient satisfaction, customer loyalty.